A facile fabrication method for corrosion-resistant micro/nanostructures on stainless steel surfaces with tunable wettability. (1st March 2016) - Park, Byungrak; Hwang, Woonbong
Abstract: Superhydrophilic surfaces were fabricated on stainless steel surfaces via simple etching and oxidation processes and were modified by a self-assembled monolayer to provide superhydrophobic surfaces. The micro/nanostructure and reconstructed passivation layer of the stainless steel surfaces exhibited good mechanical durability and long-term stability. The corrosion resistance of the surfaces was investigated using sea water. The test results indicate that the reconstructed passivation layer of the surfaces provides excellent corrosion resistivity. The successful fabrication of large-area superhydrophilic/superhydrophobic surfaces offers the possibility of providing stainless steel surfaces with unique wetting characteristics for various industrial applications. Graphical abstract: